Temperature modulates the response of the thermophilous sea urchin Arbacia lixula early life stages to CO2-driven acidification - GIANGUZZA, Paola; GIANGUZZA, Fabrizio; VIZZINI, Salvatrice; SARA', Gianluca; Visconti, G; Dupont, S. (2014)
The increasing abundances of the thermophilous black sea urchin Arbacia lixula in the Mediterranean Sea are attributed to the Western Mediterranean warming. However, few data are available on the potential impact of this warming on A. lixula in combination with other global stressors such as ocean acidification. The aim of this study is to investigate the interactive effects of increased temperature and of decreased pH on fertilization and early development of A. lixula. This was tested using a fully crossed design with four temperatures (20, 24, 26 and 27 C) and two pH levels (pHNBS 8.2 and 7.9). Temperature and pH had no significant effect on fertilization and larval survival (2d) for temperature <27 C. At 27 C, the fertilization success was very low (<1%) and all larvae died within 2d. Both temperature and pH had effects on the developmental dynamics. Temperature appeared to modulate the impact of decreasing pH on the % of larvae reaching the pluteus stage leading to a positive effect (faster growth compared to pH 8.2) of low pH at 20 C, a neutral effect at 24 C and a negative effect (slower growth) at 26 C. These results highlight the importance of considering a range of temperatures covering today and the future environmental variability in any experiment aiming at studying the impact of ocean acidification